Arterial Pseudoaneurysms Complicating Pancreatitis. Issue 1 (January 2015) - Verde, Franco; Fishman, Elliot K.; Johnson, Pamela T.
<x xml:space="preserve">Abstract</x> Abstract Arterial pseudoaneurysm formation of visceral arteries as a vascular complication of pancreatitis, either acute or chronic, is an uncommon phenomenon. This review article discusses the incidence, pathophysiology, imaging, treatment strategies, and prognosis of mesenteric pseudoaneurysms complicating pancreatitis.